(untitled) (Modern education and development, 2025)
The role of the English language in the field of jurisprudence is both significant and complex, especially in the context of global legal practices and international relations. In Uzbekistan, as the country continues to reform its legal system and engage more deeply with the international community, English plays an increasingly important role. This article explores the importance of English in jurisprudence, focusing on its stylistic aspects and how these contribute to the clarity, precision, and persuasiveness of legal texts, with special attention to its impact on Uzbekistan’s legal system.